2000
DOI: 10.1038/labinvest.3780116
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Receptor for Advanced Glycation End Products (RAGE) with Transthyretin Triggers Nuclear Transcription Factor kB (NF-kB) Activation

Abstract: SUMMARY:Mutated transthyretin (TTR) fibrils are associated with the pathology of familial amyloidotic polyneuropathy (FAP), in which extracellular amyloid deposits lead to degeneration of cells and tissues, in particular neurons of the peripheral nerve. Here we present evidence that the receptor for advanced glycation end products (RAGE), previously associated with Alzheimer's disease, acts as a selective cell surface acceptor site for both soluble and fibrillar TTR. Immunohistochemical studies demonstrating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 36 publications
4
123
0
3
Order By: Relevance
“…Imunohistochemical studies showing increased expression of RAGE in FAP tissues, initially suggested the relevance of this receptor to fibrillar TTR-induced pathology. In fact, the binding of aggregated TTR to RAGE was shown to trigger the activation of the transcription factor NF-kB inducing an inflammatory and apoptotic cascade of events (36). As such, it was predicted that in vivo, the association of TTR with RAGE in the cells of FAP patients would lead to neurodegeneration.…”
Section: Ttr Interaction With the Receptor For Advanced Glycation Endmentioning
confidence: 99%
“…Imunohistochemical studies showing increased expression of RAGE in FAP tissues, initially suggested the relevance of this receptor to fibrillar TTR-induced pathology. In fact, the binding of aggregated TTR to RAGE was shown to trigger the activation of the transcription factor NF-kB inducing an inflammatory and apoptotic cascade of events (36). As such, it was predicted that in vivo, the association of TTR with RAGE in the cells of FAP patients would lead to neurodegeneration.…”
Section: Ttr Interaction With the Receptor For Advanced Glycation Endmentioning
confidence: 99%
“…RAGE also interacts with other endogenous non-glycated peptide ligands including S100/calgranulin 56 , amphoterin (also termed as high mobility group box 1 protein, HMGB1) 57,58 , amyloid fibrills 59 , transthyretin 60 , and a leukocyte integrin, Mac-1 61 , many of which are important inflammatory regulators. Some of these inflammatory ligands for RAGE may be involved in pathogenesis of obesity and metabolic syndrome.…”
Section: Endogenous Rage Ligands Insulin Resistance and Metabolic Symentioning
confidence: 99%
“…9 In human FAP nerves, when cytotoxicity of nonfibrillar TTR was assessed by immunohistochemistry for inflammation and oxidative stress-associated molecules, we observed in-creased axonal expression of these markers, showing that early aggregates, in a presymptomatic phase, are toxic to cells. 8,10 This toxicity is most probably related to activation of nuclear factor (NF)-B by TTR aggregates, 11 as some inflammation-and oxidative stress-related molecules are targets of the NF-B transcription factor, 12 and activation of NF-B is found at sites of TTR deposition in FAP nerves. 11 To understand the mechanisms underlying fibril formation, deposition, and cytotoxic effects caused by aggregates, many questions remain to be investigated.…”
mentioning
confidence: 99%
“…8,10 This toxicity is most probably related to activation of nuclear factor (NF)-B by TTR aggregates, 11 as some inflammation-and oxidative stress-related molecules are targets of the NF-B transcription factor, 12 and activation of NF-B is found at sites of TTR deposition in FAP nerves. 11 To understand the mechanisms underlying fibril formation, deposition, and cytotoxic effects caused by aggregates, many questions remain to be investigated. In an attempt to gain insights in the pathogenesis of FAP, several groups have generated transgenic mice carrying the human TTR Val30Met gene.…”
mentioning
confidence: 99%